Aiolos Overexpression in Systemic Lupus Erythematosus B Cell Subtypes and BAFF-Induced Memory B Cell Differentiation Are Reduced by CC-220 Modulation of Cereblon Activity - Nakayama, Yumi (J Immunol, 2017)
BAFF is a B cell survival and maturation factor implicated in the pathogenesis of systemic lupus erythematosus (SLE). In this in vitro study, we describe that soluble BAFF in combination with IL-2 and IL-21 is a T cell contact-independent inducer of human B cell proliferation, plasmablast differentiation, and IgG secretion from circulating CD27(+) memory and memory-like CD27(−)IgD(−) double-negative (DN) B cells, but not CD27(−)IgD(+) naive B cells. In contrast, soluble CD40L in combination with IL-2 and IL-21 induces these activities in both memory and naive B cells. Blood from healthy donors and SLE patients have similar circulating levels of IL-2, whereas SLE patients exhibit elevated BAFF and DN B cells and reduced IL-21. B cell differentiation transcription factors in memory, DN, and naive B cells in SLE show elevated levels of Aiolos, whereas Ikaros levels are unchanged. Treatment with CC-220, a modulator of the cullin ring ligase 4-cereblon E3 ubiquitin ligase complex, reduces Aiolos and Ikaros protein levels and BAFF- and CD40L-induced proliferation, plasmablast differentiation, and IgG secretion. The observation that the soluble factors BAFF, IL-2, and IL-21 induce memory and DN B cell activation and differentiation has implications for extrafollicular plasmablast development within inflamed tissue. Inhibition of B cell plasmablast differentiation by reduction of Aiolos and Ikaros may have utility in the treatment of SLE, where elevated levels of BAFF and Aiolos may prime CD27(+) memory and DN memory-like B cells to become Ab-producing plasmablasts in the presence of BAFF and proinflammatory cytokines.